(untitled) (New York, 1999)
Molecular Systematics and Plant Evolution discusses the diversity and evolution of plants with a molecular approach. It looks at population genetics, phylogeny (history of evolution) and developmental genetics, to provide a framework from which to understand evolutionary patterns and relationships amongst plants. The international panel of contributors are all respected systematists and evolutionary biologists, who have brought together a wide range of topics from the forefront of research while keeping the text accessible to students. It has been written for senior undergraduates, postgraduates and researchers in the fields of botany, systematics, population / conservation genetics, phylogenetics and evolutionary biology.
Keywords: Plants,Thực vật; Classification,Molecular aspects,Phân loại,Khía cạnh phân tử